Motivation and Job Satisfaction of Tutors in Colleges of Education in the Central Region of Ghana (International Journal of Scientific Research and Management (IJSRM), 2020)
The study sought to examine the present disposition of the tutors of the colleges of education, with regard to their present and future job motivation and satisfaction. The research design for the study is a cross-sectional survey design. The population of the study was all the academic staff of three Colleges of Education namely, OLA College of Education, Fosu College of Education and Komenda College of Education. OLA College of Education has 58 tutors, Komenda College of Education has 42 tutors and Fosu College of Education has 52 tutors. The total population of all the three colleges summed up to 152 tutors. The sample for the study was made up of all the 152 tutors in the three colleges of education. The sampling technique used was census. The main data collection instrument was questionnaire and interview. The results of the study indicate that tutors of colleges of education in the central region had high career expectations. The study also revealed that human resource policies, reward systems, incentives available to tutors and the roles played by tutor associations do exist in colleges of education in the central region of Ghana. The human resource policies ensured staff welfare, job security, promote opportunities for training and ensure good working conditions. This policy has however not generally been able to provide tutors with the required motivation they need to effectively carry out their duties. It was recommended that tutor associations should work more assiduously to ensure that the welfare of the members are respected and taken into due consideration by the college administration to ensure that tutors are motivated well enough to carry out their responsibilities.Motivation